Comparative Genomics of Flowering Time Pathways Using Brachypodium distachyon as a Model for the Temperate Grasses - Higgins, Janet A. (Public Library of Science, 2010)
Brachypodium distachyon (Brachypodium) is a model for the temperate grasses which include important cereals such as barley, wheat and oats. Comparison of the Brachypodium genome (accession Bd21) with those of the model dicot Arabidopsis thaliana and the tropical cereal rice (Oryza sativa) provides an opportunity to compare and contrast genetic pathways controlling important traits. We analysed the homologies of genes controlling the induction of flowering using pathways curated in Arabidopsis Reactome as a starting point. Pathways include those detecting and responding to the environmental cues of day length (photoperiod) and extended periods of low temperature (vernalization). Variation in these responses has been selected during cereal domestication, providing an interesting comparison with the wild genome of Brachypodium. Brachypodium Bd21 has well conserved homologues of circadian clock, photoperiod pathway and autonomous pathway genes defined in Arabidopsis and homologues of vernalization pathway genes defined in cereals with the exception of VRN2 which was absent. Bd21 also lacked a member of the CO family (CO3). In both cases flanking genes were conserved showing that these genes are deleted in at least this accession. Segmental duplication explains the presence of two CO-like genes in temperate cereals, of which one (Hd1) is retained in rice, and explains many differences in gene family structure between grasses and Arabidopsis. The conserved fine structure of duplications shows that they largely evolved to their present structure before the divergence of the rice and Brachypodium. Of four flowering-time genes found in rice but absent in Arabidopsis, two were found in Bd21 (Id1, OsMADS51) and two were absent (Ghd7, Ehd1). Overall, results suggest that an ancient core photoperiod pathway promoting flowering via the induction of FT has been modified by the recruitment of additional lineage specific pathways that promote or repress FT expression.